Kurikulum Pendidikan Sejarah di India - Naijan Naijan (Jurnal Pendidikan Sejarah, 2015)
Schooling educational system in India uses system 5-3-2-2 in level, Lower Primary School for 5 years(class I-V), Upper Primary School for 3 years (classs VI-VIII), Secondary School 2 for years (class IXX),Higher Secondary School for 2 years (class XI-XII). Educational Curriculum ruled by a nationalcurriculum named National Curriculum Framework 2005 produced by National Council of EducationalResearch and Training (NCERT). NCERT is a governmental institution which hold education in India.NCERT is an institution belongs to Human Resource Development Ministry. Relating to the historysubject in the Indian Schools, the government puts it as an important subject, mainly for increasing thestudent’s nationalisme attitude. For this reason, the government makes the history as a compulsry subjecfor all level of school education in India, particularly the National History for class I - XII. Meanwhilethe World History taught only from class I until class X only.